Aneurysmal Remodeling in the Circle of Willis after Carotid Occlusion in an Experimental Model. Issue 3 (March 2014) - Tutino, Vincent M; Mandelbaum, Max; Choi, Hoon; Pope, Liza C; Siddiqui, Adnan; Kolega, John; Meng, Hui
Carotid occlusions are associated with de novo intracranial aneurysm formation in clinical case reports, but this phenomenon is not widely studied. We performed bilateral carotid ligation ( n =9) in rabbits to simulate carotid occlusion, and sham surgery ( n =3) for control. Upon euthanasia ( n =3 at 5 days, n =6 at 6 months post ligation, and n =3 at 5 days after sham operation), vascular corrosion casts of the circle of Willis (CoW) were created. Using scanning electron microscopy, we quantified gross morphologic, macroscopic, and microscopic changes on the endocasts and compared findings with histologic data. At 5 days, CoW arteries of ligated animals increased caliber. The posterior communicating artery (PCom) increased length and tortuosity, and the ophthalmic artery (OA) origin presented preaneurysmal bulges. At 6 months, calibers were unchanged from 5 days, PComs further increased tortuosity while presenting segmental dilations, and the OA origin and basilar terminus presented preaneurysmal bulges. This exploratory study provides evidence that flow increase after carotid occlusion produces both compensatory arterial augmentation and pathologic remodeling such as tortuosity and saccular/fusiform aneurysm. Our findings may have considerable clinical implications, as these lesser-known consequences should be considered when managing patients with carotid artery disease or choosing carotid ligation as a therapeutic option.